2006
DOI: 10.6026/97320630001153
|View full text |Cite
|
Sign up to set email alerts
|

Protein beta-turn assignments

Abstract: Abstract:A classical way to analyze protein 3D structures or models is to investigate their secondary structures. Their predictions are also widely used as a help to build new 3D models. Thus, hundreds of prediction methods have been proposed. Nonetheless before predicting, secondary structure assignment is required even if not trivial. Therefore numerous but diverging assignment methods have been developed. β-turns constitute the third most important secondary structures. However, no analysis to compare the β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 16 publications
2
28
0
Order By: Relevance
“…They are as recurrent as the PolyProline helix II conformation 34 or the frequent types of b-turns. 35 Chan and coworkers 16 analyzed only 362 b-bulges from 170 proteins. In this work, the dataset used is 66 times bigger, nevertheless a similar distribution of b-bulges was found (see Supporting Information Table S1).…”
Section: Analysis Of the Secondary Structuresmentioning
confidence: 99%
“…They are as recurrent as the PolyProline helix II conformation 34 or the frequent types of b-turns. 35 Chan and coworkers 16 analyzed only 362 b-bulges from 170 proteins. In this work, the dataset used is 66 times bigger, nevertheless a similar distribution of b-bulges was found (see Supporting Information Table S1).…”
Section: Analysis Of the Secondary Structuresmentioning
confidence: 99%
“…These results show the difficulties for defining an appropriate length for α-helices, β-strands and coils and locating their ends. Another recent study has also shown the consequences of this differences on β-turn assignment [255]. DEFINE always remains distinct from all these methods because it over-assigns regular secondary structure and, with respect to this, is closer to PALSSE than the other SSAMs.…”
Section: Secondary Structuresmentioning
confidence: 99%
“…In the same way, analysis of PUs in terms of secondary structures did not show any significant tendency in comparison to the entire databank. The Protein Blocks [56,75,85,88,99,[101][102][103][104][105][106][107][108] give a finer description than secondary structures [109], they so give more precise description of protein contacts and even some insights in signature of specific regions of protein loops in the PUs (e.g., PBs h and i).…”
Section: Discussionmentioning
confidence: 99%